The conformation of lysozyme in solution - Dobson, C; Dobson, Christopher Martin (1975)
﻿ This thesis describes an investigation of the conformation of a small protein, lysozyme from hen egg-white, in aqueous solution which was carried out by means of nuclear magnetic resonance (nmr) spectroscopy. The conformation in the crystalline state had previously been investigated by X-ray diffraction, and a model of this conformation (the X-ray structure) was available. The solution and crystalline states could therefore be compared. Before conformational studies could be undertaken, several problems associated with the nmr spectroscopy of a protein had to be overcome. The spectrum of lysozyme (in this work 1H resonances were studied) consists of a large number of broad overlapping lines. The individual resonances needed to be resolved and then assigned to specific protons in the molecule. Two different methods were devised to increase the resolution of the spectrum. First, the linewidths of resonances were reduced by a factor of about two by a mathematical manipulation of the spectrum (convolution difference). Secondly, the number of resonances observed in any given spectrum was reduced. This was achieved either by difference spectroscopy (the subtraction of two slightly different spectra) or by use of specific sequences of rf pulses in the Fourier transform nmr experiment. Using these methods, about sixty resonances were completely and separately resolved.